800MPa-grade high-strength steel wire material for electric arc additive manufacturing as well as preparation method and application of 800MPa-grade high-strength steel wire material

By using a specially made 800MPa grade high-strength steel wire in arc additive manufacturing, combined with "double vacuum" smelting method and coating treatment technology, the problem of degradation of the strength, toughness and corrosion resistance of the formed parts caused by traditional materials is solved, and forming parts with high strength, high toughness and good corrosion resistance are achieved.

CN119571216APending Publication Date: 2025-03-07CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411712939.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the existing arc additive manufacturing technology, arc additive manufacturing is used with traditional commercial welding materials, resulting in a decrease in the strength, toughness and corrosion resistance of the formed parts.

Method used

A 800MPa grade high-strength steel wire material is provided, and its components include C, Si, Mn, Ni, Cr, Mo, V, Ti, Sn, Cu and other elements, and is prepared by "double vacuum" smelting method and coating treatment technology, for arc additive manufacturing.

Benefits of technology

By optimizing the composition and preparation process, the yield strength, tensile strength and low-temperature impact absorption energy of the forming parts are significantly improved, while enhancing its corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571216A_ABST
    Figure CN119571216A_ABST
Patent Text Reader

Abstract

The invention relates to an 800MPa-grade high-strength steel wire for electric arc additive manufacturing and a preparation method and application thereof, and belongs to the field of materials for electric arc additive manufacturing. The high-strength steel wire comprises, by mass, 0.03%-0.10% of C, 0.4%-0.8% of Si, 1.50%-2.20% of Mn, 2.7%-3.5% of Ni, 0.50%-0.80% of Cr, 0.50%-1.00% of Mo, smaller than or equal to 0.001% of V, smaller than or equal to 0.05% of Ti, 0.01%-0.03% of Sn, smaller than or equal to 0.015% of Cu, smaller than or equal to 0.008% of P, smaller than or equal to 0.008% of S, smaller than or equal to 0.005% of O, smaller than or equal to 0.005% of N, smaller than or equal to 0.001% of H and the balance Fe. According to the low-alloy high-strength steel wire, by adding Cr and Mo, dispersed carbide precipitation can be formed, and then the strength and toughness of steel are improved; meanwhile, by adding a very small amount of alloy elements such as Ti and V, the content of carbides of the formed part in the material adding process is increased, so that grains are refined, and the strength and toughness of the formed part are further improved; and by adding a small amount of Sn and Cu, the corrosion resistance of a formed part is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of materials for arc additive manufacturing, and in particular to an 800MPa-grade high-strength steel wire for arc additive manufacturing, and a preparation method and application thereof. Background Art

[0002] Low alloy high strength steel is widely used in large ships and offshore engineering platforms because of its low manufacturing cost and high strength performance. However, with the development of the shipbuilding industry and the increase in the demand for marine rights, higher requirements are placed on the material properties and structural parts preparation processes of ships and offshore engineering platforms. Based on the performance requirements of high strength, high toughness, corrosion resistance, etc. of structural parts, simplified preparation processes, and improved material utilization, the new arc additive manufacturing technology has a good application prospect in the shipbuilding industry.

[0003] Arc additive manufacturing uses wire to achieve near-net shape of parts through arc surfacing, which can simplify traditional casting, forging, rolling, machining and other processes, making it have the characteristics of short production cycle and high material utilization rate. At present, the preparation method of marine high-strength steel parts is still traditional, and arc additive manufacturing is occasionally used to prepare parts, but the wire used is mainly used for welding to prepare the formed components, and the composition and preparation method of the wire are developed based on the characteristics of welding. The equipment used for arc additive manufacturing is basically the same as that used for welding, and the working conditions are similar, but there are obvious differences. Welding is a limited number of passes of arc welding to connect the base material and the welding material, which involves the problem of base material dilution, and its heat accumulation is much smaller than that of arc additive manufacturing; while arc additive manufacturing is the remelting of the wire itself, and its heat accumulation is much more serious than welding. Therefore, if traditional commercial welding materials are used for arc additive manufacturing, severe heat accumulation will cause the size of the formed parts to be large, and serious burning will occur during the additive manufacturing process. The strength and toughness of the formed parts will decrease, and the formed parts made of existing wire materials have poor corrosion resistance, which will affect their service life as marine parts. Summary of the invention

[0004] In view of the above analysis, the embodiments of the present invention aim to provide an 800 MPa grade high-strength steel wire for arc additive manufacturing and a preparation method and application thereof, so as to solve the problems of low strength, poor toughness and poor corrosion resistance of formed parts produced by arc additive manufacturing using existing wires.

[0005] On the one hand, an embodiment of the present invention provides an 800MPa grade high-strength steel wire for arc additive manufacturing. The high-strength steel wire includes, by mass percentage: C: 0.03-0.10%, Si: 0.4-0.8%, Mn: 1.50-2.20%, Ni: 2.7-3.5%, Cr: 0.50-0.80%, Mo: 0.50-1.00%, V: ≤0.001%, Ti: ≤0.05%, Sn: 0.01-0.03%, Cu: ≤0.015%, P: ≤0.008%, S: ≤0.008%, O: ≤0.005%, N: ≤0.005%, H: ≤0.001%, and Fe is the balance.

[0006] Furthermore, the high-strength steel wire includes, by mass percentage, the following: C: 0.05-0.07%, Si: 0.4-0.6%, Mn: 1.50-1.80%, Ni: 2.7-3.5%, Cr: 0.50-0.60%, Mo: 0.70-0.90%, Sn: 0.03%, Cu: ≤0.015%, V: 0.001%, Ti: 0.05%, P: ≤0.008%, S: ≤0.008%, O: ≤0.005%, N: ≤0.005%, H: ≤0.001%, and Fe as the balance.

[0007] Furthermore, the mass percentage of Cu and Sn in the high-strength steel wire satisfies Cu / Sn≥0.5.

[0008] Furthermore, the surface of the high-strength steel wire has a coating, and the components of the coating include NiSO4, NiCl2, H3BO4, and TiO2.

[0009] On the other hand, an embodiment of the present invention provides a method for preparing an 800 MPa grade high-strength steel wire for arc additive manufacturing, which is used to prepare the high-strength steel wire of the above embodiment, and the method comprises:

[0010] S1, performing vacuum induction melting on the raw materials to obtain molten steel;

[0011] S2, pouring the molten steel to cast into electrode rod material;

[0012] S3, performing vacuum consumable arc melting on the electrode rod material, and obtaining a rod ingot by casting;

[0013] S4, forging the bar ingot, and rolling the forged bar to prepare a wire rod;

[0014] S5, annealing the wire rod and then water cooling it;

[0015] S6, drawing the wire rod to prepare a wire material.

[0016] Furthermore, the preparation method also includes: S7, coating the wire, and the components of the coating include NiSO4, NiCl2, H3BO4, and TiO2.

[0017] Preferably, NiSO4, NiCl2, H3BO4, TiO2 in the coating = 7-8:3-5:2-4:1-3.

[0018] Furthermore, in step S3, after the electrode rod is machined to remove the oxide scale, vacuum consumable arc melting is performed, and during melting, the voltage is adjusted to 30-40V and the current is adjusted to 2-6kA.

[0019] Furthermore, step S6 includes: performing a coating treatment on the wire rod after pickling to remove the oxide scale; drawing the wire rod after the coating treatment, and performing online annealing during the drawing process, with the annealing temperature being 1100-1200°C.

[0020] Furthermore, in step S4, the bar ingot is homogenized at 1050-1200°C and then forged.

[0021] On the other hand, an embodiment of the present invention further provides an application of 800MPa grade high-strength steel wire, wherein the high-strength steel wire of the above embodiment is used for arc additive manufacturing to obtain a formed part; the yield strength of the formed part is ≥800MPa, the tensile strength is ≥850MPa, and the low-temperature impact absorption energy of -50°C is ≥50J.

[0022] Furthermore, in arc additive manufacturing, the wire feeding speed is 3.0 to 9.0 m / min, and the scanning speed is 0.20 to 0.35 m / min.

[0023] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0024] 1. The low-alloy high-strength steel wire of the present invention has a low C content, which can significantly reduce the crack sensitivity of the high-strength steel formed part by reducing the C content; by adding Cr and Mo, dispersed carbide precipitation can be formed, thereby improving the strength and toughness of the steel; at the same time, by adding a very small amount of alloying elements such as Ti and V, the carbide content of the formed part during the additive process is increased, thereby refining the grains and further improving the strength and toughness of the formed part.

[0025] 2. The alloy element Sn is added to the low-alloy high-strength steel wire of the present invention, and SnO2 is formed at the local corrosion position during the service of the formed component to inhibit the corrosion of the substrate. In the later corrosion process, the content of the dense α-FeOOH product formed is increased, which plays a good barrier role and improves the corrosion resistance of the formed component. At the same time, a small amount of Cu element is added to the wire, and the Cu element can be deposited on the surface of the steel to form a rust layer with protective properties, thereby improving the corrosion resistance of the substrate.

[0026] 3. The Cu in the low-alloy high-strength steel wire of the present invention can produce a synergistic effect with the Sn element to improve the corrosion resistance of the steel; wherein, Cu can promote the initiation of local pitting corrosion but inhibit the expansion of pitting corrosion, while the Sn element promotes the growth of pitting corrosion but inhibits the initiation of pitting corrosion. By controlling the mass fraction ratio of the two to be approximately Cu / Sn≥0.5, the corrosion rate of the steel can be significantly reduced.

[0027] 4. The present invention adopts a "double vacuum" melting method when preparing high-strength steel wire, namely vacuum induction melting and vacuum consumable arc furnace melting, which guarantees the high-purity smelting of high-strength steel and the quality of wire to the greatest extent. Compared with electroslag remelting, the method of the present invention has higher control accuracy on oxygen and nitrogen elements, and can reduce the content and size of inclusions such as oxides and sulfides, thereby improving the toughness of formed parts.

[0028] 5. The present invention performs coating treatment on the surface of the prepared high-strength steel wire, which can improve the process adaptability of the wire and greatly reduce the splashing of the molten pool during the arc additive manufacturing process.

[0029] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0031] Figure 1 This is a microstructure diagram of the formed part of Example 1 of the present invention.

[0032] Figure 2 This is a surface morphology of the rust layer of the formed part in Example 1 of the present invention.

[0033] Figure 3 This is a local corrosion morphology diagram of the formed part in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0035] An embodiment of the present invention provides an 800MPa grade high-strength steel wire for arc additive manufacturing, which includes the following components C in percentage by mass: 0.03-0.10%, Si: 0.4-0.8%, Mn: 1.50-2.20%, Ni: 2.7-3.5%, Cr: 0.50-0.80%, Mo: 0.50-1.00%, V: ≤0.001%, Ti: ≤0.05%, Sn: 0.01-0.03%, Cu: ≤0.015%, P: ≤0.008%, S: ≤0.008%, O: ≤0.005%, N: ≤0.005%, H: ≤0.001%, and Fe as the balance.

[0036] The low-alloy high-strength steel wire material of the present invention has a low C element content, and the crack sensitivity of the high-strength steel formed part can be greatly reduced by reducing the C content; by adding appropriate amounts of Cr and Mo, dispersed carbide precipitation can be formed, thereby improving the strength and toughness of the steel; at the same time, by adding very small amounts of alloying elements such as Ti and V, the carbide content of the formed part during the additive process is increased, thereby refining the grains and further improving the strength and toughness of the formed part.

[0037] Specifically, the C element is a strong solid solution strengthening element in the wire, which can significantly improve the yield strength of high-strength steel. If the amount of C added is too high, the arc additive manufacturing process will have a greater tendency to crack and be prone to cracking; if the C content exceeds 0.2%, the strength will be too high and its low-temperature impact toughness will be significantly reduced; and if the C content is too low, it will be unfavorable for the solid solution strengthening effect. Therefore, in order to ensure resistance to strong heat accumulation and reduce cracking tendency during the additive manufacturing of arc fuses for large components, the present invention designs the C content in the wire to be 0.03-0.10%.

[0038] As an alloying element in steel, the mass fraction of Si is generally not less than 0.4%, which can significantly improve the elastic limit, yield strength and yield strength ratio of steel; at the same time, Si can also improve the hardenability of steel to obtain a higher content of strengthened structure. In the arc additive manufacturing process, the heating and cooling speed of the molten pool is relatively fast. If the Si content is too high, its toughness will decrease. Therefore, the content of Si should not be too high and should be controlled between 0.4 and 0.8%.

[0039] The main functions of Mn are deoxidation and desulfurization. In the present invention, Mn can enhance the deoxidation and desulfurization effects by deoxidizing in combination with Si, thereby reducing the size and content of inclusions in high-strength steel. Considering the adverse effects of Mn on the strength and plasticity of formed components, the Mn content is controlled between 1.50 and 2.20%.

[0040] Ni is an austenite stabilizing element, which can promote the formation of more martensite / bainite mixed structure in high-strength steel at room temperature, has significant structure strengthening function, and can also improve the toughness of the material. However, when the Ni content exceeds 4%, it is easy to cause the formation of combined bainite structure in the formed part, resulting in unstable toughness. Therefore, the Ni element is controlled at 2.5-3.5%.

[0041] Cr and Mo are both ferrite-forming elements, which can reduce the critical phase transition temperature from austenite to ferrite, reduce the diffusion capacity of C, and improve the hardenability of weld metal; and Cr can also increase the uniform corrosion resistance of steel. When Cr and Mo coexist, dispersed carbides can be formed, thereby significantly improving the strength and toughness of steel. However, too high Cr content will cause brittleness of formed parts and reduce toughness.

[0042] Trace amounts of V and Ti elements can refine the grains in steel, and at the same time form carbides with C elements to produce precipitation strengthening; Ti elements can form fine dispersed titanium carbides in steel, refine martensite and bainite structures, and play a precipitation strengthening role; the fine dispersed carbides precipitated by the two under the heat accumulation of arc additive manufacturing can greatly improve the strength and toughness of components. However, when the V and Ti content is too high, it will reduce the martensite transformation temperature range, promote bainite transformation, form granular bainite, and reduce the toughness of steel. Therefore, the V content is controlled to ≤0.001% and the Ti content is controlled to ≤0.05%.

[0043] A small amount of Sn element can combine with oxygen to form SnO2 during the service of the formed parts, inhibiting the corrosion of the matrix. In the later corrosion process, SnO2, Fe, α-FeOOH and graphite (SnO2-MG) composite corrosion products will be formed, forming a good barrier effect, which can significantly improve the long-term corrosion resistance of low-alloy high-strength steel. However, its content should not be too high. Too high a content will form large-particle oxides at the grain boundary and in the grain, reducing the mechanical properties and toughness of the component. Therefore, its content is controlled at 0.01-0.03%.

[0044] Specifically, when a small amount of Sn element is contained in the formed part, Sn(OH)2 will be formed first in an acidic environment, which is an unstable phase, and then it will be transformed into Sn(OH)4, and then dehydrated to form SnO2. The entire corrosion cycle of the formed part is divided into three stages, including the initial corrosion, the middle corrosion and the late corrosion. The initial corrosion stage mainly focuses on the protective effect of the initial corrosion products formed on the corrosion-prone areas of the alloy steel, and the late corrosion stage mainly focuses on the protective effect of the composite corrosion products formed on the steel matrix. In a corrosive environment, a large amount of H + and C1 - On the surface of the matrix, the SnO2 phase will be enriched at the grain boundaries and high-energy grain boundaries. As the corrosion reaction proceeds, a stable SnO2-MG composite product phase will be formed on the surface of the matrix, inhibiting corrosion behavior and improving corrosion resistance. In the final corrosion stage, the SnO2-MG composite product becomes denser and more stable, and the thickness of the composite product remains basically unchanged in the later stage of corrosion. The corrosion resistance tends to be stable and has a downward trend.

[0045] The Cu element can stabilize the austenite phase and can replace Ni in steel to reduce its content, which is of great significance for saving economic costs. At the same time, the Cu element can also significantly improve the uniform corrosion resistance of steel. Cu can be deposited on the surface of steel, thereby inhibiting anodic dissolution; it can form a protective rust layer (Cu2O, CuO, CuCl) on the surface of low-carbon steel to improve the corrosion resistance of the matrix. However, too high a Cu content will reduce the plasticity and toughness of the steel and produce "hot brittleness", that is, it is easy to crack during high-temperature forging. At the same time, the low content control of the Cu element in shipbuilding steel helps to improve the radiation resistance of steel materials. Therefore, the Cu content is controlled to ≤0.015% after comprehensive consideration.

[0046] In some embodiments, the mass percentages of Cr and Mo in the high-strength steel wire satisfy Cr / Mo=0.8-1.6. In the present invention, the appropriate mass fractions of Mo and Cr affect the composition of carbides (M2C), thereby reducing the mismatch between carbides and the matrix, making the carbides more dispersed in the matrix, thereby improving the corrosion resistance and toughness of the steel.

[0047] In some embodiments, the mass percentage of Cu and Sn in the high-strength steel wire satisfies Cu / Sn≥0.5. Among them, Cu can produce a synergistic effect with the Sn element to improve the corrosion resistance of the steel. Cu can promote the initiation of local pitting corrosion but inhibit the expansion of pitting corrosion, while the Sn element can promote the growth of pitting corrosion but inhibit the initiation of pitting corrosion. When the mass fraction ratio of the two is about Cu / Sn≥0.5, the corrosion rate of the steel can be significantly reduced.

[0048] Preferably, the high-strength steel wire comprises, by mass percentage, the following: C: 0.05-0.07%, Si: 0.4-0.6%, Mn: 1.50-1.80%, Ni: 2.7-3.5%, Cr: 0.50-0.60%, Mo: 0.70-0.90%, V: 0.001%, Ti: 0.05%, Sn: 0.03%, Cu: ≤0.015%, P: ≤0.008%, S: ≤0.008%, O: ≤0.005%, N: ≤0.005%, H: ≤0.001%, and Fe is the balance.

[0049] The embodiment of the present invention also provides a method for preparing 800MPa grade high-strength steel wire for arc additive manufacturing, so as to prepare the high-strength steel wire of the above embodiment. The preparation method specifically comprises the following steps:

[0050] S1, performing vacuum induction melting on the raw materials to obtain molten steel;

[0051] S2, casting the molten steel into electrode rod material;

[0052] S3, performing vacuum consumable arc melting on the electrode rod material, and obtaining a rod ingot by casting;

[0053] S4, forging the bar ingot, and rolling the forged bar for multiple passes to prepare a wire rod;

[0054] S5, annealing the wire rod and then water cooling it;

[0055] S6, drawing the wire rod to prepare a wire material.

[0056] The present invention adopts a "double vacuum" melting method when preparing high-strength steel wire, namely vacuum induction melting and vacuum consumable arc furnace melting, which guarantees the high-purity smelting of high-strength steel and the quality of wire to the greatest extent. Compared with electroslag remelting, the method of the present invention has higher control accuracy on oxygen, nitrogen and sulfur elements, and can reduce the content and size of inclusions such as oxides and sulfides, thereby improving the toughness of formed parts.

[0057] In step S1, a vacuum induction furnace may be used to perform primary smelting on the raw materials to obtain molten steel. To ensure that the content of impurity elements in the molten steel is low, the vacuum degree is controlled to be maintained at ≤10Pa during vacuum induction melting.

[0058] In step S2, when pouring the molten steel, a vacuum pouring method is adopted to prevent oxygen addition and ensure that the oxygen content in the electrode rod material formed by casting is low.

[0059] In some embodiments, the tapping temperature of the molten steel during pouring is 1640-1650° C. to ensure the smoothness of the pouring process. Too high or too low tapping temperature is not conducive to the smoothness of pouring.

[0060] In step S3, after the electrode bar is machined to remove the oxide scale, vacuum consumable arc melting is performed to avoid introducing impurities into the bar. The present invention further deoxidizes and denitrifies the electrode bar by vacuum consumable arc melting, and can obtain a highly clean bar ingot, and can control the oxygen and nitrogen contents in the wire to be below 0.005%, and the sulfur content to be below 0.008%, and can further reduce the content and size of inclusions such as oxides and sulfides, thereby improving the toughness of the formed part.

[0061] In some embodiments, the electrode rod material can be put into a vacuum consumable arc furnace for secondary vacuum melting. During melting, the voltage can be adjusted to 30-40V and the current can be adjusted to 2-6kA to ensure that the melting furnace has a suitable temperature so that the molten steel has good fluidity, enhances the stirring effect of the molten pool, helps to remove impurities and gases in the molten pool, and improves the purity of the ingot.

[0062] In step S4, the bar ingot is first heated and kept warm at a temperature of 1050-1200°C for 2-3 hours to homogenize the ingot and ensure the uniformity of the internal structure of the material for subsequent forging; then the bar ingot is forged and the final forging temperature is controlled to be ≥950°C, and air cooling is performed after forging. For example, the bar ingot can be forged into a bar with a diameter of 50 mm.

[0063] In some embodiments, the forged bar material may be subjected to multiple rolling at 850-1050° C. to obtain a wire rod. For example, the wire rod may be rolled into a wire rod with a diameter of 8 mm.

[0064] In step S5, when the wire rod is annealed, the annealing temperature is 1100-1200°C, and the annealing time is 1-2 hours. Keeping the wire rod warm at this temperature can further ensure the uniformity of the internal structure of the wire rod.

[0065] In step S6, the wire rod is first pickled to remove the surface oxide scale, and after being washed and dried, the wire rod is subjected to a coating treatment. After the coating treatment, a phosphate-based film is formed on the surface of the wire rod, which is porous and can better absorb lubricants, thereby forming an effective lubricating film during the drawing process, reducing friction, wear and cracking, and improving wear resistance. After the coating treatment, the wire rod is dried, and the drying temperature can be 100-150°C.

[0066] The wire rod after film treatment is drawn, and online annealing is performed during the drawing process. The annealing temperature is 1100-1200°C. The hardness and strength of the wire rod can be reduced by online annealing to facilitate drawing. After multiple drawing passes, the wire rod can be prepared into a wire with a diameter of 1.2mm or 1.6mm.

[0067] In some embodiments, the preparation method further includes step S7, coating the prepared wire, wherein the components of the coating include NiSO4, NiCl2, H3BO4, and TiO2. The present invention forms a coating containing the above components on the surface of the wire by coating the wire, thereby improving the process adaptability of the wire and greatly reducing the splash of the molten pool during the arc additive manufacturing process.

[0068] Preferably, the ratio of NiSO4, NiCl2, H3BO4 and TiO2 in the coating is 7-8:3-5:2-4:1-3.

[0069] The embodiment of the present invention also provides an application of 800MPa grade high-strength steel wire. Specifically, the high-strength steel wire of the above embodiment can be subjected to arc additive manufacturing to obtain a formed part. The yield strength of the formed part is ≥800MPa, the tensile strength is ≥850MPa, and the low-temperature impact absorption energy of -50°C is ≥50J.

[0070] In some embodiments, arc additive manufacturing equipment may be used for arc additive manufacturing, such as a Fronius CMT welder. The substrate material used in arc additive manufacturing is 800MPa grade low alloy high strength steel, and the plate thickness may be 15 to 30mm.

[0071] In some embodiments, in arc additive manufacturing, the current is 120A to 280A, the arc voltage is 21V to 27V, the scanning speed is 0.20 to 0.35m / min, the wire feeding speed is 3.0 to 9.0m / min, and the shielding gas is Ar+5%CO2 or 100%Ar. Among them, the faster the scanning speed, the finer the structure of the formed part, the higher the strength, but the poorer the toughness; the greater the wire feeding speed, the greater the amount of fuse, the greater the current, the coarser the structure of the formed part, and the strength and toughness are both unfavorable. On the whole, by optimizing the process parameters in arc additive manufacturing within the above range, a formed part with uniform and fine structure, high strength and high toughness can be obtained.

[0072] The following examples are used to further illustrate the 800 MPa grade high-strength steel wire material of the present invention and its preparation method and application.

[0073] Example 1

[0074] The 800 MPa grade high-strength steel wire for arc additive manufacturing in this embodiment includes, by mass percentage, the following: C: 0.05%, Si: 0.5%, Mn: 1.80%, Ni: 3.0%, Cr: 0.63%, Mo: 0.6%, V: 0.001%, Ti: 0.03%, Sn: 0.02%, Cu: 0.015%, P: ≤0.008%, S: ≤0.008%, O: ≤0.005%, N: ≤0.005%, H: ≤0.001%, and Fe is the balance.

[0075] The preparation method of 800MPa grade high-strength steel in this embodiment includes:

[0076] (1) Vacuum induction melting: A vacuum induction furnace is used for the initial melting. To ensure a low content of impurity elements, the vacuum degree is maintained at 10 Pa.

[0077] (2) Pouring rods: The molten steel is vacuum poured at a tapping temperature of 1645°C to form electrode rods;

[0078] (3) Vacuum consumable arc melting: The electrode bar is machined to remove the 2 mm thick oxide scale on the surface, and then placed in a vacuum consumable arc furnace for secondary vacuum melting. By adjusting the current to 30 V and the voltage to 4 kA, further deoxidation and denitrification melting are performed, and then casting is performed to obtain a high-clean bar ingot;

[0079] (4) High temperature forging and rolling: The obtained high-clean bar is subjected to high temperature forging. After the bar is kept at 1100°C for 2 hours, it is forged into a bar with a diameter of 50 mm. The final forging temperature is 950°C, and then air-cooled. The forged bar is rolled at a high temperature of 1050°C for multiple passes to prepare a wire rod with a diameter of 8 mm.

[0080] (5) Annealing treatment: keep the wire rod at 1150°C for 2 hours and then water cool it;

[0081] (6) Wire drawing: After the water cooling zone is completed, the wire rod is pickled and treated with a film; the wire rod is heated to 1100°C and subjected to multiple wire reduction drawing, with the diameter decreasing from 6.5mm→4.9mm→3.2mm→1.6mm→1.2mm to form a wire with a diameter of 1.2mm; after water washing, drying, and finally coiling and packaging, the wire is prepared. The composition of the prepared wire is shown in Table 1.

[0082] (7) Coating treatment: The surface of the wire is subjected to coating treatment, and the coating composition includes NiSO4, NiCl2, H3BO4, TiO2=8:4:3:2.

[0083] The wire prepared in this embodiment is additively manufactured using an arc additive manufacturing device, the device is a Fronius Advance welder, and the substrate material is 800MPa-grade low-alloy high-strength steel with a thickness of 30mm. In the arc additive manufacturing, the current is 240A, the arc voltage is 25V, the scanning speed is 0.35m / min, the wire feeding speed is 7.0m / min, and the shielding gas is Ar+5%CO2.

[0084] The formed parts are sampled in a direction parallel to the scanning path to prepare tensile specimens and low-temperature impact toughness specimens.

[0085] like Figure 1 As shown, from the microstructure diagram of the formed part, dispersed carbides such as vanadium carbide and titanium carbide can be observed, which is beneficial to refine the grains and improve the strength and toughness of the formed part.

[0086] After a period of service, a rust layer forms on the surface of the molded part. Figure 2 The local rust layer on the surface of the formed part is irradiated by scanning electron microscope to obtain the local corrosion morphology, such as Figure 3 As shown, there are a large number of dense SnO2-MG composite products in the corrosion area on the surface of the formed part, which inhibits the further corrosion behavior of the formed part.

[0087] Example 2

[0088] The 800 MPa grade high-strength steel wire for arc additive manufacturing in this embodiment includes, by mass percentage, the following: C: 0.10%, Si: 0.6%, Mn: 2.00%, Ni: 3.5%, Cr: 0.80%, Mo: 0.90%, V: 0.001%, Ti: 0.05%, Sn: 0.02%, Cu: 0.015%, P: ≤0.008%, S: ≤0.008%, O: ≤0.005%, N: ≤0.005%, H: ≤0.001%, and Fe is the balance.

[0089] The preparation method of 800MPa grade high-strength steel in this embodiment includes:

[0090] (1) Vacuum induction melting: A vacuum induction furnace is used for the initial melting. To ensure a low content of impurity elements, the vacuum degree is maintained at 8Pa;

[0091] (2) Pouring rods: The molten steel is vacuum poured at a tapping temperature of 1640°C to form electrode rods;

[0092] (3) Vacuum consumable arc melting: The electrode bar is machined to remove the 2 mm thick oxide scale on the surface, and then placed in a vacuum consumable arc furnace for secondary vacuum melting. By adjusting the current to 35 V and the voltage to 6 kA, further deoxidation and denitrification melting are performed, and then casting is performed to obtain a high-clean bar ingot;

[0093] (4) High temperature forging and rolling: The obtained high-clean bar is subjected to high temperature forging. After the bar is kept at 1200°C for 2 hours, it is forged into a bar with a diameter of 50 mm. The final forging temperature is 1000°C, and then air-cooled. The forged bar is rolled at a high temperature of 850°C for multiple passes to prepare a wire rod with a diameter of 8 mm.

[0094] (5) Annealing treatment: keep the wire rod at 1100°C for 2 hours and then water cool it;

[0095] (6) Wire drawing: After the water cooling zone is completed, the wire rod is pickled and treated with a film; the wire rod is heated to 1150°C and subjected to multiple wire reduction drawing, with the diameter decreasing from 6.5 mm to 4.9 mm to 3.2 mm to 1.6 mm, to form a wire with a diameter of 1.6 mm; after water washing, drying, and finally coiling and packaging, the wire is prepared. The composition of the prepared wire is shown in Table 1.

[0096] (7) Coating treatment: The surface of the wire is subjected to coating treatment, and the coating composition includes NiSO4, NiCl2, H3BO4, TiO2=7:5:2:1.

[0097] The wire prepared in this embodiment is additively manufactured using an arc additive manufacturing device, the device is a Fronius Advance welder, and the substrate material is 800MPa-grade low-alloy high-strength steel with a thickness of 30mm. In the arc additive manufacturing, the current is 220A, the arc voltage is 24V, the scanning speed is 0.30m / min, the wire feeding speed is 6.0m / min, and the shielding gas is Ar+5%CO2.

[0098] The formed parts are sampled in a direction parallel to the scanning path to prepare tensile specimens and low-temperature impact toughness specimens.

[0099] Example 3

[0100] The 800 MPa grade high-strength steel wire for arc additive manufacturing in this embodiment includes, by mass percentage, the following: C: 0.03%, Si: 0.4%, Mn: 2.20%, Ni: 2.70%, Cr: 0.50%, Mo: 0.50%, V: 0.001%, Ti: 0.04%, Sn: 0.03%, Cu: 0.015%, P: ≤0.008%, S: ≤0.008%, O: ≤0.005%, N: ≤0.005%, H: ≤0.001%, and Fe is the balance.

[0101] The preparation method of 800MPa grade high-strength steel in this embodiment includes:

[0102] (1) Vacuum induction melting: A vacuum induction furnace is used for the initial melting. To ensure a low content of impurity elements, the vacuum degree is maintained at 7Pa;

[0103] (2) Pouring rods: The molten steel is vacuum poured at a tapping temperature of 1650°C to form electrode rods;

[0104] (3) Vacuum consumable arc melting: The electrode bar is machined to remove the 2 mm thick oxide scale on the surface, and then placed in a vacuum consumable arc furnace for secondary vacuum melting. By adjusting the current to 40 V and the voltage to 2 kA, further deoxidation and denitrification melting are performed, and then casting is performed to obtain a high-clean bar ingot;

[0105] (4) High temperature forging and rolling: The obtained high-clean bar is subjected to high temperature forging. After the bar is kept at 1050°C for 2 hours, it is forged into a bar with a diameter of 50 mm. The final forging temperature is 950°C, and then air-cooled. The forged bar is rolled for multiple passes at a high temperature of 950°C to prepare a wire rod with a diameter of 8 mm.

[0106] (5) Annealing treatment: keep the wire rod at 1200℃ for 2h and then water cool it;

[0107] (6) Wire drawing: After the water cooling zone is completed, the wire rod is pickled and treated with a film; the wire rod is heated to 1200°C, and the wire rod is reduced in diameter through multiple passes, and the diameter is reduced from 6.5mm→4.9mm→3.2mm→1.6mm→1.2mm to form a wire with a diameter of 1.2mm; after water washing, drying, and finally coiling and packaging, the wire is prepared. The composition of the prepared wire is shown in Table 1.

[0108] The wire prepared in this embodiment is additively manufactured using an arc additive manufacturing device, the device being a Fronius Advance welder, and the substrate material is 800 MPa-grade low-alloy high-strength steel with a plate thickness of 30 mm.

[0109] In the arc additive manufacturing, the current is 200A, the arc voltage is 23V, the scanning speed is 0.30m / min, the wire feeding speed is 5.0m / min, and the shielding gas is 100% Ar. In this embodiment, the wire surface is not coated, and during the arc additive manufacturing process, the molten pool splashes more.

[0110] The formed parts are sampled in a direction parallel to the scanning path to prepare tensile specimens and low-temperature impact toughness specimens.

[0111] Example 4

[0112] The difference between this embodiment and embodiment 1 is that the 800 MPa grade high-strength steel wire for arc additive manufacturing includes, by mass percentage, the following: C: 0.06%, Si: 0.80%, Mn: 1.50%, Ni: 3.20%, Cr: 0.63%, Mo: 1.0%, V: 0.001%, Ti: 0.04%, Sn: 0.01%, Cu: 0.015%, P: ≤0.008%, S: ≤0.008%, O: ≤0.005%, N: ≤0.005%, H: ≤0.001%, and Fe is the balance.

[0113] Example 5

[0114] The difference between this embodiment and embodiment 1 is that the 800 MPa grade high-strength steel wire for arc additive manufacturing includes, by mass percentage, the following: C: 0.06%, Si: 0.5%, Mn: 1.70%, Ni: 3.3%, Cr: 0.6%, Mo: 0.7%, V: 0.001%, Ti: 0.05%, Sn: 0.03%, Cu: 0.015%, P: ≤0.008%, S: ≤0.008%, O: ≤0.005%, N: ≤0.005%, H: ≤0.001%, and Fe is the balance.

[0115] Example 6

[0116] The difference between this embodiment and embodiment 1 is that in the 800 MPa grade high strength steel wire material for arc additive manufacturing, Sn: 0.03%, Cu: 0.01%, Cu / Sn<0.5.

[0117] Comparative Example 1

[0118] The difference compared with Example 1 is that the wire material of this comparative example does not contain Sn.

[0119] Comparative Example 2

[0120] The difference compared with Example 1 is that the wire material of this comparative example does not contain Cu.

[0121] Comparative Example 3

[0122] The difference compared with Example 1 is that the Sn content in the wire material of this comparative example is excessive, which is 0.04%.

[0123] Comparative Example 4

[0124] The difference compared with Example 1 is that the Cu content in the wire of this comparative example is excessive, which is 0.02%.

[0125] Comparative Example 5

[0126] The difference compared with Example 1 is that the wire material of this comparative example does not contain V.

[0127] Comparative Example 6

[0128] The difference compared with Example 1 is that the wire material of this comparative example does not contain Ti.

[0129] Comparative Example 7

[0130] The difference compared with Example 1 is that the V content in the wire material of this comparative example is excessive, which is 0.002%.

[0131] Comparative Example 8

[0132] The difference compared with Example 1 is that the Ti content in the wire of this comparative example is excessive, which is 0.06%.

[0133] Comparative Example 9

[0134] The difference compared with Example 1 is that when the wire material of this comparative example is manufactured into a formed part by arc additive manufacturing, the scanning speed is 0.5 m / min and the wire feeding speed is 9.5 m / min.

[0135] Comparative Example 10

[0136] The difference compared with Example 1 is that when the wire material of this comparative example is manufactured into a formed part by arc additive manufacturing, the scanning speed is 0.15 m / min and the wire feeding speed is 2.5 m / min.

[0137] Comparative Example 11

[0138] The difference compared with Example 1 is that in the wire preparation method of this comparative example, the electroslag remelting method is adopted in the secondary smelting.

[0139] The composition contents of the high-strength steel wires of various embodiments and comparative examples are shown in Table 1.

[0140] Table 1 Wire material composition of each embodiment (mass percentage wt.%)

[0141] C Si Mn Ni Cr Mo V Ti Sn Cu Example 1 0.05 0.50 1.80 3.00 0.63 0.60 0.001 0.03 0.02 0.015 Example 2 0.10 0.60 2.00 3.50 0.80 0.90 0.001 0.05 0.02 0.015 Example 3 0.03 0.40 2.20 2.70 0.50 0.50 0.001 0.04 0.03 0.015 Example 4 0.06 0.80 1.50 3.20 0.63 1.00 0.001 0.04 0.01 0.015 Example 5 0.06 0.50 1.70 3.30 0.60 0.70 0.001 0.05 0.03 0.015 Example 6 0.05 0.50 1.80 3.00 0.63 0.60 0.001 0.03 0.03 0.010 Comparative Example 1 0.05 0.50 1.80 3.00 0.63 0.60 0.001 0.03 / 0.015 Comparative Example 2 0.05 0.50 1.80 3.00 0.63 0.60 0.001 0.03 0.02 / Comparative Example 3 0.05 0.50 1.80 3.00 0.63 0.60 0.001 0.03 0.04 0.015 Comparative Example 4 0.05 0.50 1.80 3.00 0.63 0.60 0.001 0.03 0.02 0.02 Comparative Example 5 0.05 0.50 1.80 3.00 0.63 0.60 / 0.03 0.02 0.015 Comparative Example 6 0.05 0.50 1.80 3.00 0.63 0.60 0.001 / 0.02 0.016 Comparative Example 7 0.05 0.50 1.80 3.00 0.63 0.60 0.002 0.03 0.02 0.015 Comparative Example 8 0.05 0.50 1.80 3.00 0.63 0.60 0.001 0.06 0.02 0.015

[0142] Tensile and toughness specimens were taken from the formed parts of each embodiment and comparative example in a direction parallel to the scanning path, and tensile and low-temperature impact toughness tests were performed, and the test results are shown in Table 2. According to Table 2, each element in Examples 1 to 6 is within a suitable range, so that it has excellent mechanical properties and corrosion resistance, the yield strength is above 810MPa, the tensile strength is above 855MPa, the -50℃ low-temperature impact absorption energy is above 80KV2, and the annual average corrosion rate is below 0.45mm / a.

[0143] Since Comparative Examples 1 and 2 do not contain Sn or Cu, their corrosion resistance is relatively poor; in Comparative Examples 3 and 4, the content of Sn or Cu is too high, resulting in a decrease in low-temperature impact absorption energy, that is, poor toughness. In Comparative Examples 5 and 6, since they do not contain V or Ti, the dispersed carbides in the formed parts are reduced, and the yield strength and low-temperature impact absorption energy are reduced; in Comparative Examples 7 and 8, the content of V or Ti is too high, and although the yield strength and tensile strength of the formed parts are improved compared to Example 1, the impact toughness is poor. In Comparative Examples 9 and 10, the welding speed and wire feeding speed are not within the appropriate process range, resulting in defects in the forming in arc additive manufacturing, and the strength and toughness of the formed parts are poor.

[0144] Table 2 Mechanical properties and corrosion resistance of wire forming parts in various embodiments

[0145]

[0146]

[0147] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. An 800MPa grade high-strength steel wire for arc additive manufacturing, characterized in that: The high-strength steel wire comprises, by mass percentage, the following: C: 0.03-0.10%, Si: 0.4-0.8%, Mn: 1.50-2.20%, Ni: 2.7-3.5%, Cr: 0.50-0.80%, Mo: 0.50-1.00%, V: ≤0.001%, Ti: ≤0.05%, Sn: 0.01-0.03%, Cu: ≤0.015%, P: ≤0.008%, S: ≤0.008%, O: ≤0.005%, N: ≤0.005%, H: ≤0.001%, and Fe is the remainder.

2. The high-strength steel wire according to claim 1, characterized in that: The high-strength steel wire comprises, by mass percentage, C: 0.05-0.07%, Si: 0.4-0.6%, Mn: 1.50-1.80%, Ni: 2.7-3.5%, Cr: 0.50-0.60%, Mo: 0.70-0.90%, Sn: 0.03%, Cu: ≤0.015%, V: 0.001%, Ti: 0.05%, P: ≤0.008%, S: ≤0.008%, O: ≤0.005%, N: ≤0.005%, H: ≤0.001%, and Fe is the remainder.

3. The high-strength steel wire according to claim 1 or 2, characterized in that: The mass percentage of Cu and Sn in the high-strength steel wire satisfies Cu / Sn≥0.

5.

4. The high-strength steel wire according to claim 1 or 2, characterized in that: The surface of the high-strength steel wire is provided with a coating, and the components of the coating include NiSO4, NiCl2, H3BO4, and TiO2.

5. A method for preparing 800MPa grade high-strength steel wire for arc additive manufacturing, used for preparing the high-strength steel wire according to any one of claims 1 to 4, characterized in that: include: S1, performing vacuum induction melting on the raw materials to obtain molten steel; S2, pouring the molten steel to form electrode rod material; S3, performing vacuum consumable arc melting on the electrode rod material, and obtaining a rod ingot by casting; S4, forging the bar ingot, and rolling the forged bar to prepare a wire rod; S5, annealing the wire rod, and then water cooling it; S6, drawing the wire rod to prepare a wire material.

6. The preparation method according to claim 5, characterized in that: Also includes: S7, coating the wire, wherein the coating comprises NiSO4, NiCl2, H3BO4, and TiO2; Preferably, in the coating, NiSO4, NiCl2, H3BO4, TiO2=7-8:3-5:2-4:1-3.

7. The preparation method according to claim 5, characterized in that: In step S3, after the electrode rod material is machined to remove oxide scale, vacuum consumable arc melting is performed, and during melting, the voltage is adjusted to 30-40V and the current is adjusted to 2-6kA.

8. The preparation method according to claim 5, characterized in that: Step S6 includes: After the wire rod is pickled to remove the oxide scale, a film treatment is performed; The wire rod after coating treatment is drawn, and online annealing is performed during the drawing process, with the annealing temperature being 1100-1200°C.

9. The preparation method according to claim 5, characterized in that: In step S4, the bar ingot is homogenized at 1050-1200°C and then forged.

10. An application of 800MPa high-strength steel wire, characterized in that: The high-strength steel wire according to any one of claims 1 to 4 is used for arc additive manufacturing to obtain a formed part; the yield strength of the formed part is ≥800MPa, the tensile strength is ≥850MPa, and the low-temperature impact absorption energy of -50°C is ≥50J.